Lipopolysaccharide‐induced hypothalamic inflammation in cancer cachexia‐anorexia is amplified by tumour‐derived prostaglandin E2. Issue 6 (27th October 2022) - Li, Xiaolin; Holtrop, Tosca; Jansen, Fleur A.C.; Olson, Brennan; Levasseur, Pete; Zhu, Xinxia; Poland, Mieke; Schalwijk, Winni; Witkamp, Renger F.; Marks, Daniel L.; van Norren, Klaske
Abstract: Background: Cachexia‐anorexia syndrome is a complex metabolic condition characterized by skeletal muscle wasting, reduced food intake and prominent involvement of systemic and central inflammation. Here, the gut barrier function was investigated in pancreatic cancer‐induced cachexia mouse models by relating intestinal permeability to the degree of cachexia. We further investigated the involvement of the gut–brain axis and the crosstalk between tumour, gut and hypothalamus in vitro. Methods: Two distinct mouse models of pancreatic cancer cachexia (KPC and 4662) were used. Intestinal inflammation and permeability were assessed through fluorescein isothiocyanate dextran (FITC‐dextran) and lipopolysaccharide (LPS), and hypothalamic and systemic inflammation through mRNA expression and plasma cytokines, respectively. To simulate the tumour–gut–brain crosstalk, hypothalamic (HypoE‐N46) cells were incubated with cachexia‐inducing tumour secretomes and LPS. A synthetic mimic of C26 secretome was produced based on its secreted inflammatory mediators. Each component of the mimic was systematically omitted to narrow down the key mediator(s) with an amplifying inflammation. To substantiate its contribution, cyclooxygenase‐2 (COX‐2) inhibitor was used. Results: In vivo experiments showed FITC‐dextran was enhanced in the KPC group (362.3 vs. sham 111.4 ng/mL, P < 0.001). LPS was increased to 140.9 ng/mL in the KPC group, compared with sham and 4662 groups (115.8 and 115.8 ng/mL, P < 0.05). Hypothalamic inflammatory gene expression of Ccl2 was up‐regulated in the KPC group (6.3 vs. sham 1, P < 0.0001, 4662 1.3, P < 0.001), which significantly correlated with LPS concentration ( r = 0.4948, P = 0.0226). These data suggest that intestinal permeability is positively related to the cachexic degree. Prostaglandin E2 (PGE2) was confirmed to be present in the plasma and PGE2 concentration (log10) in the KPC group was much higher than in 4662 group (1.85 and 0.56 ng/mL, P < 0.001), indicating a role for PGE2 in pancreatic cancer‐induced cachexia. Parallel to in vivo findings, in vitro experiments revealed that the cachexia‐inducing tumour secretomes (C26, LLC, KPC and 4662) amplified LPS‐induced hypothalamic IL‐6 secretion (419%, 321%, 294%, 160%). COX‐2 inhibitor to the tumour cells reduced PGE2 content (from 10 5 to 10 2 pg/mL) in the secretomes and eliminated the amplified hypothalamic IL‐6 production. Moreover, results could be reproduced by addition of PGE2 alone, indicating that the increased hypothalamic inflammation is directly related to the PGE2 from tumour. Conclusions: PGE2 secreted by the tumour may play a role in amplifying the effects of bacteria‐derived LPS on the inflammatory hypothalamic response. The cachexia‐inducing potential of tumour mice models parallels the loss of intestinal barrier function. Tumour‐derived PGE2 might play a key role in cancer‐related cachexia‐anorexia syndrome via tumour–gut–brain crosstalk.